Enriched calanoid copepods Acartia tonsa (Dana, 1849) enhances growth, survival, biochemical composition and morphological development during larval first feeding of the orchid dottyback Pseudochromis fridmani (Klausewitz, 1968) - Andrea Martino; Daniel Montero; Javier Roo; Pedro Castro; Silvia Lavorano; Francisco Otero-Ferrer (Aquaculture Reports)
In a time of unprecedented coral reef decline, improved aquaculture protocols and high-quality live feeds may contribute to the sustainability of the ornamentals industry producing new valuable and stronger specimens bred under controlled conditions, mitigating the pressure on wild natural stocks. In the present study, the effect of microalgae enriched live feed diets (15 ind. mL−1), the copepod Acartia tonsa and the rotifer Brachionus plicatilis, were tested on early larvae stages (0–15 days post hatch) of the orchid dottyback Pseudochromis fridmani. Enriched A. tonsa significantly improved P. fridmani larval growth, survival, biochemical composition, as well as the morphological development of liver, intestine and skeletal system, compared to rotifers treatment. The results obtained showed that is feasible to totally replace the enriched rotifer B. plicatilis with the enriched copepod A. tonsa during first larval feeding of orchid dottybacks, resulting in a more robust larvae with better culture performance. Indeed, feeding larvae with enriched A. tonsa avoid the different negative effects when used enriched rotifers diets, which led to liver steatosis and nuclear pyknosis, delays in intestine and skeletal development, altered proximate composition and FA content. This study provided valuable information about rearing and breeding under controlled conditions of P. fridmani, contributing to its mass scale production and to the implementation of new hatchery protocols employing high quality live feeds.